Phosphorus acquisition capacity and size trait evolution in Achillea wilhelmsii reflect adaptation to environmental gradients - Mostafa Farajpour; Mohsen Ebrahimi; Mohammad Sadat-Hosseini; Shahab Mirinejad; Mahmoud-Reza Ramezanpour; Sepideh Sanjari (Scientific Reports)
Abstract Understanding how plant traits evolve in response to environmental gradients is critical for elucidating mechanisms of local adaptation. This study investigated trait variation in Achillea wilhelmsii accessions from eight climatically diverse Iranian locations after cultivation under uniform conditions. Key traits—plant size, biomass, and phosphorus content—reflect adaptive divergence along an integrated environmental gradient (PCA1) derived from temperature, precipitation, and altitude. Warmer/drier, lower-altitude conditions corresponded with reduced phosphorus uptake and smaller plant size, while cooler/wetter, higher-altitude conditions favored increased phosphorus absorption and larger plant size. Principal component analyses revealed that 62.85% of observed trait variation arises from evolutionary responses via genetic divergence, driven by natural selection across environmental gradients. Populations from colder, high-altitude sites (positive PCA1 scores) evolved enhanced phosphorus uptake, likely due to selection on pre-existing genetic variation for cold tolerance, facilitating larger plant sizes. These patterns highlight how adaptation, as an inherent capacity of plants to respond to selection pressures, shapes trait divergence under environmental heterogeneity. Future studies should dissect the genetic architecture linking phosphorus metabolism, environmental gradients, and plant size evolution.